Short Communication: Morphological variation of Coffea liberica from Batangas, Philippines with implications for sustainable coffee production and breeding programs - ABIGAIL MANGUIAT BALAN; PHEBE P. MENDOZA; ALAN RODELLE M. SALCEDO; GRECEBIO JONATHAN D. ALEJANDRO (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Balan AM, Mendoza PP, Salcedo ARM, Alejandro GJD. 2026. Short Communication: Morphological variation of Coffea liberica from Batangas, Philippines with implications for sustainable coffee production and breeding programs. Biodiversitas 26 (1): d270149. https://doi.org/10.13057/biodiv/d270149. Coffea liberica, locally known as "kapeng barako" in the Philippines, represents an understudied yet economically significant coffee species with unique morphological characteristics and climate resilience. Despite its commercial presence across Southeast Asia and potential for specialty markets, comprehensive morphological assessments of Philippine C. liberica population remain limited. This single-site baseline study provides morphometric analysis of plants grown in Batangas, Philippines, investigating correlations between leaf architecture, fruit morphology, and bean characteristics to inform breeding and sustainable cultivation. Twelve coffee plants from a farm in Barangay Ludlod, Lipa, Batangas, were analyzed using standardized morphometric protocols. Statistical analyses included correlation analysis and ANOVA to examine relationships among leaf area, cherry volume, bean dimensions, and pulp thickness. Strong positive correlations were observed between leaf area and both cherry volume (r = 0.84, p<0.05) and bean volume (r = 0.92, p<0.05), indicating coordinated morphological development. Cherry and bean volumes showed moderate correlation, while pulp thickness correlated positively with both cherry and bean volumes and accounted for over half of variation in both traits. ANOVA revealed statistically significant differences in cherry size among individual plants, though the overall range of variation was relatively narrow compared to reported diversity in other coffee species. These findings establish baseline morphometric data for C. liberica from this site, demonstrating coordinated leaf-fruit development that may guide selection criteria for breeding. Results highlight the need for expanded multi-site studies to validate these relationships for improved productivity and climate adaptation strategies.